Using smartphones as a social constructivist pedagogical tool for inquiry-supported problem-solving: an exploratory study. (1st October 2020) - Lötter, Melissa Jeanette; Jacobs, Lorette
ABSTRACT: To incorporate a rich, comprehensive and well-established framework for an advanced learning pedagogy, this study focuses on the use of smartphones as a social constructivism tool for inquiry-supported problem solving in a first-year adventure destinations module at a Tshwane Higher Education Institution (HEI). Results obtained through quantitative data collection and analysis methods indicate that student learning is enhanced through the use of smartphones as a tool to promote collaborative learning. Findings propose the adoption of new technologies in the learning process, with adventure tourism students adjusting their social networking traditions to include academic learning practices, supported by tools that enhance collaborative/networked learning and teamwork. Findings also suggest that HEIs may potentially save costs by encouraging adventure tourism students to Bring Your Own Device (BYOD) for teaching and learning purposes. This will avail more funding to support students who do not own mobile technology tools. This will close the digital divide and increase the motivation for seeking lifelong learning opportunities.